Uniaxial Testing of Soil–Cement Composites to Obtain Correlations to Be Used in Numerical Modeling - Małgorzata Jończyk-Szostek; Piotr Kanty; Jarosław Rybak; Jakub Saloni; Karolina Trybocka (Applied Sciences, 2023)
This paper presents the results of laboratory testing of samples obtained from soil–cement composite columns produced on a real-world test site as part of a research and development project. The introduction presents the motivation of the research and the goals that guided the layout of a research program. The general geotechnical conditions, initially assumed methodology of soil–cement composite sampling, and finally, the methodology of strength tests were presented. In tests conducted with the measurement of the strain-stress path, the strength and stiffness of the material were determined in various modes of the stress–strain path, including unloading/reloading cycles. The test results were presented in the form of graphs presenting soil–cement composite stiffness in the function of material strength and subjected to a short critical discussion against the background of reference samples from composites prepared in laboratory conditions. This allowed for their qualitative and quantitative assessment and the formulation of conclusions and guidelines, concerning the execution of works and especially the potential practical outcomes (benefits for numerical modeling), juxtaposed in the summary. Some prospects and needs for future developments were also formulated on the basis of actual experience.